Recent Progress on Rapid Lateral Flow Assay-Based Early Diagnosis of COVID-19 - Zhang, Ying; Chai, Yujuan; Hu, Zulu; Xu, Zhourui; Li, Meirong; Chen, Xin; Yang, Chengbin; Liu, Jia (Frontiers in Bioengineering and Biotechnology, 2022)
The outbreak of Coronavirus Disease 2019 (COVID-19) has brought enormous losses to the world. With the effective control measurement and vaccination, the prevention and curb are very fruitful, but the outbreak has not been eliminated. Therefore, it is necessary to develop a simple, convenient and rapid detection strategy to control the recurrence and dissemination of the disease. Taking the advantage of the low cost and simple operation, the point-of-care test (POCT) kits of COVID-19 based on lateral flow assay (LFA) have become one of the most convenient and widely used screening tool for the pathogen in hospital and at home. In this review, we introduce the essential feature of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, compare the existing detection methods, and focuse on the principles, merits and limitations of the LFAs based on viral nucleic acid, antigens and corresponding antibodies. Through summarization and analysis, a systematic comparison has been made, providing a comprehensive demonstration of LFA technology and insights to prevention and curb the pandemic of COVID-19.